Rancang Bangun Sistem Presensi Pada MTS Al – Islamiyah Menggunakan Metode Personal Extreme Programming (PXP) Berbasis Web - Siti Aulia Parasyfa, Nabila; Oka Safitri, Galuh (CV. Shofanah Media Berkah, 2025)
Attendance is part of an institution's reporting activities and includes attendance data that is managed to determine the number of attendees at an event so that stakeholders can easily find and use it whenever they need it. At MTS Al- Islamiyah Srengseng, the attendance system is still done manually, from recording attendance data to generating reports, which often leads to errors that make the reports inaccurate. Another problem is that there are many document storage problems, such as frequent loss of data or archives. With these problems, the author makes an attendance system in recording the attendance of students based on a website with a Personal Extreme Programming (PXP) method that aims to minimise the work of staff and teachers and provide insight into the use of technology by implementing the attendance system. The results and benefits of this design are to provide facilities for teachers to take attendance on students so that attendance data management becomes structured and reduces the risk of errors in student attendance data.